Shotgun metagenomics of fecal samples from children in Peru reveals frequent complex co-infections with multiple Campylobacter species. - Craig T Parker; Francesca Schiaffino; Steven Huynh; Maribel Paredes Olortegui; Pablo Peñataro Yori; Paul F Garcia Bardales; Tackeshy Pinedo Vasquez; Greisi E Curico Huansi; Katia Manzanares Villanueva; Wagner V Shapiama Lopez; Kerry K Cooper; Margaret N Kosek (Public Library of Science (PLoS), 2022)
Campylobacter spp. are a major cause of bacterial diarrhea worldwide and are associated with high rates of mortality and linear growth faltering in children living in low- to middle-income countries (LMICs). Campylobacter jejuni and Campylobacter coli are most often the causative agents of enteric disease among children in LMICs. However, previous work on a collection of stool samples from children under 2 years of age, living in a low resource community in Peru with either acute diarrheal disease or asymptomatic, were found to be qPCR positive for Campylobacter species but qPCR negative for C. jejuni and C. coli. The goal of this study was to determine if whole-genome shotgun metagenomic sequencing (WSMS) could identify the Campylobacter species within these samples. The Campylobacter species identified in these stool samples included C. jejuni, C. coli, C. upsaliensis, C. concisus, and the potential new species of Campylobacter, "Candidatus Campylobacter infans". Moreover, WSMS results demonstrate that over 65% of the samples represented co-infections with multiple Campylobacter species present in a single stool sample, a novel finding in human populations.